Marginal improvement in survival among patients diagnosed with metastatic prostate cancer in the second‐line antiandrogen therapy era - Isaac E. Kim (Wiley, 2021)
Abstract Since 2004, multiple blockbuster drugs have been approved for men with metastatic prostate cancer. Nevertheless, it has been reported that no improvement in survival was observed between 2004 and 2009. Herein, we have analyzed the SEER database to assess the survival outcome of metastatic prostate cancer patients since 2000. The results demonstrated that there was an improvement in both overall and prostate cancer‐specific survival for 4 months among men diagnosed with metastatic prostate cancer from 2010 to 2016 when compared to those in the pre‐2010 period. Interestingly, this survival benefit was limited to patients with bone and visceral metastasis (M1b and M1c stages). Collectively, our observation suggests that despite the new treatment agents such as second‐line antiandrogen therapies introduced in the modern era, the improvement in survival of metastatic prostate cancer patients has been surprisingly small.